The quality of working life affecting organizational commitment of university staff - Chermkhuntod, Sompop (Nimitmai Review Journal, 2021)
This research paper aims to (1)To study the quality of working life that affects the organization of university staff (2)Create a model for the development of quality of working life that affects the organizational commitment of the university's staff. This research is a mixed-method research by studying the documents In-depth interviews and questionnaires were used with 400 Rajabhat University staff. The seminar was based on experts by 9 experts. The results of the research revealed that (1) The quality of working life was in high to low level. Ordered as follows In collaboration and relationships with other people The development of the ability of a person On the balance between work and personal life Democracy in the organization Jobs that are beneficial to society Security and job progress In terms of receiving sufficient and fair remuneration for work And working conditions that are considered to be safe and promote health. (2) The model for the development of quality of working life that affects the organizational commitment of university staff has 7 components, which are Leadership of executives Salary and compensation Democracy in the organization Security and progress Development of knowledge and capability On the balance between work and personal life And the physical environment